Pengaruh Kompetensi Terhadap Kinerja Guru Yang Dimediasi Oleh Semangat Kerja (Studi Pada Guru SMK YPM 3 Taman Sidoarjo) - Chamariah Chamariah; Bambang Adi Susanto; Rudi Winarko (Universitas 45 Surabaya, 2023)
Bambang Adi Susanto, 2023. The Competence on Teacher Performance Mediated by Work Enthusiasm (Study on YPM 3 Taman Sidoarjo Vocational School teachers), Wijaya Putra University Postgraduate Program. This type of research is explanatory, namely to test the hypotheses between the hypothesized variables that will be tested for truth. the research approach used is quantitative, the research sample is 46 respondents. Data analysis used SPSS analysis and PLS Program SEM analysis. The aims of this study were: 1) To test and analyze whether competence has a direct effect on the morale of teachers at SMK YPM 3 Taman Sidoarjo; 2) To test and analyze whether competence has a direct effect on teacher performance at SMK YPM 3 Taman Sidoarjo; 3) To test and analyze whether teacher morale has a direct effect on teacher performance at SMK YPM 3 Taman Sidoarjo; 4) To test and analyze whether competence has an indirect effect on teacher performance at SMK YPM 3 Taman Sidoarjo which is mediated by morale. The results showed that: 1) Competence has a direct effect on the morale of teachers at SMK YPM 3 Taman Sidoarjo, as evidenced by the original sample value of 0.440 and the p-value of 0.043; 2) Competence has a direct effect on teacher performance at SMK YPM 3 Taman Sidoarjo, as evidenced by the original sample value of 0.238 and the p-value of 0.058; 3) Work enthusiasm has a direct effect on teacher performance at SMK YPM 3 Taman Sidoarjo, as evidenced by the original sample value of 0.468 and the p-value of 0.001; 4) Competence has an indirect effect on teacher performance at SMK YPM 3 Taman Sidoarjo which is mediated by work enthusiasm, as evidenced by the original sample value of 0.206 and the p-value of 0.005.